Pengembangan E-Modul Pendidikan Agama Islam dan Pendidikan Karakter Berbasis Lingkungan - Syafnidawati Syafnidawati; Sirajul Munir; Jamilus Jamilus; Abhanda Amra; David David; Iman Asroa B.S (AS-SABIQUN, 2026)
Islamic Religious Education (Pendidikan Agama Islam, PAI) learning at SMPN 3 Lintau Buo Utara is still dominated by conventional approaches, lacks learning modules aligned with students’ needs, does not yet integrate instruction with the surrounding learning environment, and has not fully optimized the use of technology, thereby necessitating the development of more contextual and interactive teaching materials. This study aimed to develop an environment-based PAI and Budi Pekerti e-module to support environment-based learning. The research employed a research and development method using the ASSURE model with eighth-grade students at SMPN 3 Lintau Buo Utara. Needs analysis data were collected using interview guidelines and analyzed with the Miles and Huberman technique, while validity test data were obtained through validation sheets and analyzed using Aiken’s V formula. Practicality test data consisted of quantitative data collected using student response questionnaires and analyzed with the Degree of Achievement formula, as well as qualitative data obtained through interviews and analyzed using the Miles and Huberman technique. The needs analysis results indicated that an environment-based PAI and Budi Pekerti e-module was highly necessary to develop. The resulting e-module demonstrated a high level of validity, with scores of 0.85 for media validation and 0.92 for content validation, and very high practicality with a score of 93.7 from 45 respondents, further supported by interview findings showing that the e-module was very practical for use in instruction. Accordingly, the environment-based PAI and Budi Pekerti e-module developed in this study is deemed highly valid and highly practical for implementation in classroom learning activities.